India-Pakistan Trade Normalization: the unfinished economic agenda - Taneja, Nisha; Isha Dayal (New Delhi; Springer, 2017)
This book explores the unfinished India-Pakistan Trade normalisation agenda (building upon the themes covered in the book "India-Pakistan Trade: Strengthening Economic Relations" published by Springer in 2014) and discusses the steps that must be undertaken in order to move the bilateral engagement forward. Given the commencement of bilateral state-level talks and the Indian government's emphasis on South Asian integration, it adds impetus to the trade liberalisation process, while also providing essential recommendations for policymakers in both countries
Include reference
Keywords: BUSINESS & ECONOMICS Economics General; India Commerce Pakistan; India Foreign economic relations Pakistan; Pakistan Commerce India